GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 162957205 species occurrences available in GBIF matching the query: { "BasisOfRecord" : [ "is Specimen" ] }. The dataset includes 162957205 records from 11253 constituent datasets: 16 records from Revision of the Australian leaf beetle genus Cheiloxena Baly, 1860 (Coleoptera: Chrysomelidae: Spilopyrinae). 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 28 records from Plant - Plant Virus (KIDR-PL). 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 117269 records from Coleção Entomológica do Museu Nacional / UFRJ. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 291941 records from Canadian Museum of Nature Herbarium. 964 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 3 records from A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece. 50873 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 314 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 13 records from New Species and Records of Costa Rican Featherwing Beetles (Coleoptera: Ptiliidae). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 339 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 292 records from Review of the Australian Cyllodini (Coleoptera: Nitidulidae: Nitidulinae), with descriptions of new taxa, and notes on the genus Macleayania (Nitidulini). 2812 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 82261 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 878 records from COA Bird Collection (Arctos). 122817 records from New Zealand Arthropod Collection (NZAC). 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 1 records from Cetopirus complanatus (Cirripedia: Coronulidae) from the late Middle Pleistocene human settlement of Pinnacle Point 13 B (Mossel Bay, South Africa). 18 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 10654 records from Bryophyte specimens of The Nagoya University Museum. 4 records from New species of Moluccan trichaline net-winged beetles, with remarks on the phylogenetic position and distribution of Schizotrichalus (Coleoptera: Lycidae: Metriorrhynchinae). 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 34520 records from University of Guam Insect Collection. 22857 records from National Botanic Garden Belgium - Myxomycetes. 5 records from Review of the fossil record of Bolitophilidae, with description of new taxa and discussion of position of Mangas Kovalev (Diptera: Sciaroidea). 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 9 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 3 records from Morphological and molecular characterization of three Helicotylenchus species from Iran. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 10 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 8 records from Lluciapomaresius nisae, a new species of Ephippigerini (Orthoptera: Tettigoniidae: Bradyporinae) from the northeast of the Iberian Peninsula. 3072 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 89 records from Museo de Historia Natural, Colección de Vertebrados e Invertebrados - Colección Ictiológica. 2505 records from ZUEC-ORT - Coleção de Orthoptera do Museu de Zoologia da UNICAMP. 10 records from Redescription of four species of Cytaea Keyserling, 1882 (Araneae: Salticidae). 1189 records from UWIZM Molluscs. 2 records from New species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Northeastern Region of Brazil. 5 records from Additions to the leafhopper subgenus Pediopsoides (Pediopsoides) Matsumura, 1912 (Hemiptera: Cicadellidae: Macropsinae) from Southern China. 6 records from An updated and detailed taxonomical account of the large Branchiopoda (Crustacea: Branchiopoda: Anostraca, Notostraca, Spinicaudata) from the Yale North India Expedition deposited in the Yale Peabody Natural History Museum. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 24 records from Four new free-living marine nematode species (Sabatieria) from the Chukchi Sea. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 9605 records from Aves Tanzanian collection at the Natural History Museum of Denmark (SNM). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 24370 records from Muséum d'Avignon. 626 records from Mycology collection, Norwegian Forest and Landscape Institute. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 4 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 9964 records from Plant specimens of Tama City Cultural Foundation. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 5 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 95 records from Poliquetos (Annelida: Polychaeta) del Pacífico Mexicano. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1904 records from Escarabajos coprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 8 records from NZCS Raleighvallen-Voltzberg Monitoring 1997/1998/2000/2009. 173 records from UWIZM Anoles. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 7 records from On the taxonomy and morphology of Leuthneria ruficincta (Lepidoptera: Sesiidae). 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 16 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 5279 records from Brown University. 607514 records from Plant. 4905 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 10 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 12859 records from Colecção Entomológica IIA. 30 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO. 13 records from The first data on species diversity of leeches (Hirudinea) in the Irtysh River Basin, East Kazakhstan. 4567 records from Herbarium WRSL, Main Collection. 2 records from Record of a new species of the genus Viridopromontorius Luna de Carvalho (Strepsiptera: Corioxenidae) from India with a revised key to Corioxenidae. 1 records from Eight species in the Nebela collaris complex: Nebela gimlii (Arcellinida, Hyalospheniidae), a new species described from a Swiss raised bog. 322 records from Tetranychus urticae collection records in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 7223 records from Colección Mastozoológica del IADIZA - CCT CONICET Mendoza: IADIZA-CMI. 4552 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 7116 records from DMNS Egg Collection (Arctos). 17 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 14923 records from Lepidopterous specimens of Yamagata Prefectural Museum. 7410 records from Helgeland Museum, Lepidoptera. 16449 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Ictiología. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 2777 records from Plant (KIWE-PL). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1277 records from Museu Paraense Emílio Goeldi - Chelonia Collection. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 16839 records from Colección de Poales del Museo Botánico CORD - IMBIV. 1702 records from BioGIS - Bryophytes - HUJ collections. 84 records from Revision of Tynacantha Dallas with description of two new species (Hemiptera: Heteroptera: Pentatomidae: Asopinae). 437 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 14594 records from Collection Coleoptera SMF. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1 records from A new acotylean flatworm, Armatoplana colombiana n. sp. (Platyhelminthes: Polycladida: Stylochoplanidae) from the Caribbean coast of Colombia, South America. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 3 records from The neotype of Macrostemum hyalinum (Pictet 1836) (Trichoptera: Hydropsychidae) and a key to males of Neotropical species of this genus. 94 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Mollusca (ZUFMS-MOL). 16542 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 16517 records from Shellfish specimens of the Nishinomiya Shell Museum, Japan. 2645 records from KTU Pteridophyta. 6237 records from Plecoptera. 13 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 1 records from A new species of Ferneiella from the Eocene French amber (Diptera: Scatopsidae). 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 1 records from Murcia acaroides. 216 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 280 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 34 records from NZCS Brownsberg Nature Park Monitoring. 1 records from A new species of the ant-parasitizing genus Pseudacteon Coquillett (Diptera, Phoridae) from China. 52181 records from ANTARCTIC PLANT DATABASE. 2 records from Craspedorrhynchus linardii, a new species of chewing louse (Phthiraptera: Ischnocera: Philopteridae) from the Gray-headed Kite (Aves: Falconiformes: Accipitridae). 63156 records from Field Museum of Natural History (Botany) Fungi Collection. 19 records from The family Bombyliidae in the Kingdom of Saudi Arabia (Diptera: Brachycera: Asiloidea). 1 records from Nothrus echinatus. 15610 records from SJRP - Herbário de São José do Rio Preto. 2 records from A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil. 101 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 25 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 1242 records from T. L. Hankinson Vertebrate Museum (EMU) Mammal Collection. 24 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 45 records from Morphological and genetic evolution in eastern populations of the Macrhybopsis aestivalis complex (Cypriniformes: Cyprinidae), with the descriptions of four new species. 736 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 7728 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 208 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 24 records from New species of the orb-weaving spider genus Chrysometa (Araneae, Tetragnathidae) from oak forests near of the Pico de Orizaba National Park (Veracruz, Mexico). 1952 records from ISM Ichthyology Collection. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 29 records from Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae). 9 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 27 records from A new species of crayfish in the genus Orconectes (Decapoda: Cambaridae) from the Tennessee River Drainage with comments on and key to members of the O. juvenilis Species Complex. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 4 records from Tanycarpa broadi sp. nov., a new Neotropical species of the genus Tanycarpa Foerster, 1863 (Hymenoptera: Braconidae: Alysiinae), with a key to the New World taxa. 108701 records from The Himalayan Uplands Plant database (HUP Version 1). 76380 records from DMNH Birds. 1014 records from Database on reference specimens for medicinal plants of the Euphorbiaceae family, conserved at the CNARP herbarium. 29340 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1 records from Zetes flavipes. 3 records from Amended diagnosis and redescription of Pristimantis marmoratus (Boulenger, 1900) (Amphibia: Craugastoridae), with a description of its advertisement call and notes on its breeding ecology and phylogenetic relationships. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 322 records from Collections ichtyologiques et herpétologiques (BOUM). 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 2668 records from Rutgers University, Chrysler Herbarium - Lichen Collection. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 91 records from Notes on species of the genus Chlaenius Bonelli, 1810 (Coleoptera: Carabidae, Chlaeniini) from four agro-climatic zones of Rajasthan, with description of two new species. 141 records from La collection Gilles Becquet (BOUM). 65903 records from Norwegian Lepidoptera working group. 2 records from A new cicada species of Psalmocharias Kirkaldy feeding on an Ephedra plant from China (Hemiptera: Cicadidae). 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 38876 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Notes on the biology and distribution of the tribe Agallissini in North America (Coleoptera: Cerambycidae: Cerambycinae). 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 8 records from A new four-pored Amphisbaena (Squamata: Amphisbaenidae) from northeastern Brazil. 15637 records from CCBER Herpetology Collection. 23 records from New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 506 records from Base de datos sobre los hongos anamorfos de restos de vegetales del bosque mesófilo del estado de Veracruz. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 1 records from New species of the anthiadin genus Sacura (Perciformes: Serranidae) from the Andaman Sea. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 85 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 18 records from New genus to science of Meconematinae (Orthoptera: Tettigoniidae) from China with description of two new species and proposal of one new combination. 25268 records from University of California Santa Barbara Invertebrate Zoology Collection. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 2 records from Neue Milbenarten aus Kärnten. 1 records from Nothrus biverrucatus. 8 records from A review of the taxonomy and osteology of the Rhombophryne serratopalpebrosa species group (Anura: Microhylidae) from Madagascar, with comments on the value of volume rendering of micro-CT data to taxonomists. 6780 records from Herpetofauna del Estado de Veracruz. 62997 records from Entomology Collection at the Natural History Museum of Utah. 12 records from A review of the Madagascan species of the genus Cestradoretus Ohaus (Coleoptera: Scarabaeidae: Rutelinae: Adoretini). 4 records from Four new Megaselia species (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 7 records from Speolabeo, a new genus name for the cave fish Bangana musaei (Teleostei: Cyprinidae). 3 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 14 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 20627 records from Herbier Louis-Marie (QFA) - Collection de lichens. 1877 records from Actualización de la Colección de Microorganismos de importancia acuática. 2 records from Morphology and molecules say: Tanytarsus latens, sp. nov. from Finland (Diptera: Chironomidae). 19 records from A new genus and species of natricine snake from northeast India. 6390 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 11 records from Visual Plants (144.41.33.158) - Herbarium specimens from "LOJA" Ecuador. 1 records from A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae). 890 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 113616 records from ALCB - Herbário Alexandre Leal Costa. 4 records from Ceraeocercus Uvarov, a genus recorded in China for the first time (Orthoptera, Tettigoniidae; Tettigoniinae; Drymadusini). 191799 records from Australian National Insect Collection. 3184 records from Herbarium specimens of Limoges university (LIMO). 10 records from A review of the genus Labeo (Teleostei: Cyprinidae) in Sri Lanka. 4847 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 105857 records from Fish specimens of Kagoshima University Museum. 2 records from Papuaneon, a new genus of jumping spiders from Papua New Guinea (Araneae: Salticidae: Neonini). 233 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 44 records from Rivaling the World’s Smallest Reptiles: Discovery of Miniaturized and Microendemic New Species of Leaf Chameleons (Brookesia) from Northern Madagascar. 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 13647 records from UTEP Invertebrates (Arctos). 356 records from Taxonomic revision of the species of Colletes Latreille, 1802 (Hymenoptera: Colletidae: Colletinae) found in Chile. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 10576 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 481 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 8 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 65265 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 41 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 325 records from Diversidad genética del cultivo del chile (Capsicum spp) determinada por isoenzimas y RFLP's tipos: serrano, jalapeño, manzano y silvestres en su área de distribución. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 1567 records from Flora útil del Municipio de la Huerta, Jalisco. 1703 records from Slovenian Fungal Database - Boletus informaticus. 1910 records from Chucki_Seaooplankton1953/4. 10 records from Review of the New World genus Nanium Townes, 1967 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with two new species from the Neotropical region. 215 records from The Diptera Site. 1353 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 12 records from Endogean and cavernicolous Coleoptera of the Balkans. XVII. A new species of the genus Speluncarius Reitter, 1886 (Coleoptera, Carabidae, Harpalinae, Pterostichini) from Croatia. 2 records from Two small species of Cremohipparion (Equidae, Mammalia) from Samos, Greece. 3 records from Two new brackish-water species of Macrostomum (Platyhelminthes, Macrostomida) from mangrove wetland in southern China. 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 4 records from A new genus of Silvaninae (Coleoptera: Silvanidae) with two new species from the Malay Peninsula. 74 records from Review of the horse flies of the genus Atylotus Osten Sacken, 1876 (Diptera: Tabanidae) from Egypt, with description of a new species. 10354 records from Herpetological collection of National Museum of Nature and Science. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 6 records from Moema apurinan sp. n. and Aphyolebias boticarioi sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new annual killifishes from the Rio Purus basin, Brazilian Amazon.. 23 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 49 records from Identity of bryozoan species described by Jullien & Calvet from the Bay of Biscay historically attributed to Smittia. 225278 records from Naturalis Biodiversity Center (NL) - Crustacea. 50 records from The West Palaearctic Dineura species, focussing on Sweden (Hymenoptera, Tenthredinidae). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 12147 records from Danish Ants (Formicidae). 25 records from Brown algae specimens of Komatsu City Museum. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 273 records from BMHS Herbarium Collection. 25098 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 585 records from Ascomycetes of Russian Fennoscandia. 207 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 2 records from Remarkable new fossil species of Schistostoma Becker (Diptera: Dolichopodidae Microphorinae) from mid-Cretaceous Burmese amber. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 241 records from Fishes of the Cusiana River (Meta River basin, Colombia). 3897 records from Colecção Entomológica do Departamento de Sanidade Vegetal - Ministério da Agricultura e Segurança Alimentar. 370 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 2044 records from The Broward College Insect Collection. 1926 records from Ibaraki Nature Museum, Mammals collection. 24283 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 19 records from Pterophoridae (Lepidoptera) fauna of the Republic of Tuva. 58 records from Cephalomalthinus simplicicornis (Wittmer, 1993) rev. stat. et comb. n.: a resurrected soldier beetle (Coleoptera, Cantharidae) from Taiwan based on morphological and molecular data. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 1 records from Description of a new species of Hyalinocerus (Hemiptera: Cicadellidae) from southwestern China, with an update on the generic diagnosis. 5 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 2 records from The second species of Phanoperla (Plecoptera: Perlidae) from China, P. hainana sp. nov., from Hainan Island. 121 records from Guasuctenus gen. nov., a new Neotropical spider genus of Ctenidae (Araneae). 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 59626 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 2 records from On the identity of the genus Flavoperla (Plecoptera: Perlidae), with description of a new species in southwestern China. 7 records from Description of two new species of Seinura Fuchs, 1931 (Nematoda: Aphelenchoididae) from Iran. 17 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 7 records from Sertania gen. nov., a new genus of butterflies (Lepidoptera: Riodinidae) from the South American dry diagonal. 4 records from New species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Brazil and Suriname. 2 records from New species and records of Scaphobaeocera CSIKI from New Guinea (Coleoptera: Staphylinidae: Scaphidiinae). 6 records from Re-description of two spiny clam shrimps (Crustacea: Branchiopoda: Spinicaudata) of the Indian subcontinent from Daday de Dees's collection at MNHN with new insights on the validity of Eulimnadia compressa (Baird, 1860) and Eulimnadia chaperi (Simon, 1886). 155 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 313 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 143300 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 19525 records from Bolus Herbarium: Bryophyte and Ericaceae (1641-2016). 6 records from Transfer of the Namibian Argistes africanus Simon, 1910 (Araneae: Liocranidae) to Afroceto Lyle & Haddad, 2010 (Trachelidae), with a new synonym. 8 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 1 records from Berlese's Primitive Oribatid Mites. 42 records from Arachnologie ZMK. 2 records from A new troglobitic species of Typhloroncus (Arachnida: Pseudoscorpiones: Ideoroncidae) from Guatemala. 203 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 110 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 30302 records from Mycology herbarium, Tromsø Museum. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 2 records from Description of the immature and adult stages of the jujube tube spittlebug Machaerota planitiae Distant (Hemiptera: Cercopoidea: Machaerotidae) in Bangladesh. 29 records from A review of the stink bug genus Plautia Stål from Japan (Hemiptera, Heteroptera, Pentatomidae). 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 47548 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 139635 records from ARABEL - Arachnologia Belgica. 9 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 1 records from Laubuka parafasciata, a new cyprinid fish species (Teleostei: Cyprinidae) from Mizoram northeastern India. 174 records from Antarctic pycnogonids. 62776 records from MLZ Bird Collection (Arctos). 26 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 2 records from Description of Malenchus gilanensis n. sp. from Iran. 14 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 36 records from Validity of Psammoperca datnioides Richardson 1848 and redescriptions of P. waigiensis Cuvier in Cuvier & Valenciennes 1828 and Hypopterus macropterus (Günther 1859) in the family Latidae (Perciformes) from the Indo-West Pacific. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 5 records from New records of Synallactes virgulasolida Massin & Hendrickx, 2010 (Echinodermata: Holothuroidea) from the eastern Pacific. 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 13 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 2 records from Description of the lucky Cophyla (Microhylidae, Cophylinae), a new arboreal frog from Marojejy National Park in north-eastern Madagascar. 50 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 6774 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal). 270 records from bmhs_weatherheadshell_collection. 6 records from Immature stages of the genus Oxythyrea (Coleoptera: Scarabaeidae: Cetoniinae) with a key to third instar larvae, and notes on the biology of the genus. 234 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1 records from Nemertean specimens of Ryukyu University Museum (Fujukan). 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 285727 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 6 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 35 records from Anthomyiidae, Fanniidae and Muscidae (Diptera) from the Juan Fernández Archipelago (Chile): 60 years after Willi Hennig’s contributions. 2531 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 39 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 13 records from Taxonomy of calcareous sponges (Porifera, Calcarea) sampled on artificial substrates of a recreational marina in the Tropical Northeastern Brazilian coast. 4 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 4 records from A new small-sized Theloderma (Anura: Rhacophoridae) from Laos. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 638 records from MNA (Section of Genoa) - Marine Biological Samples. 12 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). I. Gracilipalpe, morchella and nigrum groups. 351 records from UWYMV Herpetology Collection (Arctos). 38 records from Geographic structure of genetic variation in the Parachute Gecko Ptychozoon lionotum Annandale, 1905 across Indochina and Sundaland with descriptions of three new species. 104498 records from Herbarium Senckenbergianum (FR) - Fungi. 2489 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2007 records from Plant specimens of Bihoro Museum. 84 records from Museu Paraense Emílio Goeldi - Myriapoda Collection. 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 51366 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 167 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 78 records from An annotated catalogue of the pygmy grasshoppers of the genus Criotettix Bolívar 1887 (Orthoptera: Tetrigidae) with two new Criotettix species from China. 6 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 77 records from Empria and Monsoma in Japan. 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 321 records from Vegetación de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 18 records from Kinorhyncha specimens of Ryukyu University Museum (Fujukan). 394 records from Reptilia ZMK. 96405 records from Ibaraki Nature Museum, Vascular Plants collection. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 3 records from A redescription of Moina australiensis Sars, 1896 (Cladocera: Moinidae) with short notes on Australian moinids. 3 records from Hylaperdina squamosa, a new species of Neotropical Lycoperdininae (Coleoptera, Endomychidae) from Brazil. 85277 records from University of Ghana - Ghana Herbarium. 5021 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 262 records from Plants Of Nnamdi Azikiwe University Herbarium (NAUH) Awka. 911 records from Museo de Historia Natural Universidad de Caldas - Colección de Vertebrados e Invertebrados - Anfibios. 16078 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 18 records from Three new generic records and descriptions of four new species of jumping spiders (Araneae, Salticidae) from Sri Lanka. 1 records from On a new species of Euchondrus Boettger, 1883 from Syria (Pulmonata: Enidae). 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 498736 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 110 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 8110 records from Catálogo de los equinodermos recientes de México (Fase II). 3 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 17 records from ScoliorhAPis stEPAnovi - new species of sea cucumber from the North-West Pacific (Holothuroidea: Synaptida: Chiridotidae: Taeniogyrinae) and some remarks on the genus ScoliorhAPis. 10898 records from Inventario de Hymenóptera; parasítica en México. 268160 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 4 records from Amazoniaseius imparisetosus n. sp., n. g.: an unusual new phytoseiid mite (Acari: Phytoseiidae) from the Amazon forest. 3 records from Two species of the conifera - subgroup of Triconia (Copepoda, Oncaeidae) from the northeastern equatorial Pacific, with a description of the unknown male of T. hirsuta. 48 records from Onuphi s and Mooreonuphis (Annelida: Onuphidae) from West Africa with the description of three new species and the reinstatement of O. landanaensis Augener, 1918. 1 records from A new species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) on fig trees in Iran. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 1 records from Morphotaxonomic revision of species-groups of Simulium (Simulium) (Diptera: Simuliidae) in the Oriental Region. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 10 records from Sinopyrophorinae, a new subfamily of Elateridae (Coleoptera, Elateroidea) with the first record of a luminous click beetle in Asia and evidence for multiple origins of bioluminescence in Elateridae. 15774 records from Insect Collection of Saitama Museum of Natural History. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 1 records from A new edible cricket species from Africa of the genus Scapsipedus. 13 records from Two new species of lotic breeding salamanders (Amphibia, Caudata, Hynobiidae) from western Japan. 11 records from List of leaf beetles (Coleoptera: Chrysomelidae) from Lagodekhi reserve with new records for Transcaucasia and Georgia. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 27 records from A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins.. 124 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 8 records from Sandsitermes gen. nov., a new nasute termite genus from South America (Isoptera, Termitidae, Nasutitermitinae). 3712 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 10 records from SyNoeca ilheeNsis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest. 58 records from IBF Monitoring of Plant Galls. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 6 records from Discovery of two new Andean species of Scolomus (Townes & Townes), with a key to all known species (Hymenoptera: Ichneumonidae: Metopiinae). 408 records from Birds Specimens of Akita Prefectural Museum. 5 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 26841 records from MSUM Ichthyology and Herpetology Collections. 1143 records from Herpetofauna de la región El Huizache, San Luis Potosí. 3 records from Two new records of palm species for Gabon: Sclerosperma profizianum Valk. & Sunder. and Eremospatha quiquecostulata Becc.. 371 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 4 records from Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 3 records from Notes on west Palaearctic species of the genus Trigonurus Mulsant, 1847 (Coleoptera: Staphylinidae: Trigonurinae). 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 1000 records from Plant specimens of Natural History Museum, Kishiwada City. 2149 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México. 2 records from A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco. 19 records from Database on reference specimens for medicinal plants of the Araceae family, conserved at the CNARP herbarium. 48 records from A new species of Metrobates Uhler, 1871 (Hemiptera: Heteroptera: Gerridae) from Colombia. 46 records from The genera and species of the Brueelia - complex (Phthiraptera: Philopteridae) described by Mey (2017). 240 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas. 769 records from Digital Florula - Palo Verde Biological Station. 173 records from Fundación Miguel Lillo - Colección Invertebrados. 54 records from A catalog of Acroceridae (Diptera) from Chile. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 200 records from Bird specimens of Kushiro City Museum. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 8467 records from CNMT - Herbário Centro Norte Mato Grossense. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 351 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 936 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 679 records from Collection Hydrozoa - ZSM München. 40 records from Two new cichild species Neolamprologus (Teleostei: Cichlidae) from Lake Tanganyika, East Africa.. 22 records from The eel genus Macrocephenchelys (Anguilliformes: Congridae) in Taiwan, with description of a new species. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 202368 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3918 records from Collembola Collection. 16 records from A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 33454 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 1158 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 204 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 33 records from Nothogreniera new genus, for two species of Australian " Paracnephia " (Diptera: Simuliidae). 794914 records from Western Australian Museum provider for OZCAM. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 13144 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 18026 records from Colección de Hongos del Herbario de la Universidad de La Laguna: TFC Mic. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 3 records from First records of Edwardsiana sociabilis (Ossiannilsson, 1936) and Laburrus pellax (Horváth, 1903) (Hemiptera, Auchenorrhyncha: Cicadellidae) in Switzerland. 30 records from A checklist of the millipedes (Diplopoda) of Myanmar, with an updated list of Leonardo Fea’s collecting localities. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 1 records from Hymenoptera: Eucoilinae (Cynipoidea). 1 records from A new species of the genus Sazonia O. Gorbunov & Arita, 2001 from Vietnam (Lepidoptera: Sesiidae). 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4 records from Two new species of the water scavenger beetle genus Hemiosus Sharp (Coleoptera: Hydrophilidae) from Colombian Andes. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 3 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 37 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53204 records from Naturalis Biodiversity Center (NL) - Diptera. 4 records from Trachyuropodid mites (Acari: Uropodina) from South-East Asia: catalog, new key and description of two new species. 10 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 17520 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 1 records from On some Haploops species collected in the North Atlantic Ocean with the description of Haploops islandica n. sp. (Crustacea: Gammaridea: Ampeliscidae) [Contribution to the knowledge of the Haploops genus. 8.]. 188368 records from Geneva Herbarium – General Collection (G). 2 records from A new species of Tyrannoseira (Collembola: Entomobryidae: Seirini) from the Brazilian coastal region. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 271 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 4792 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 67 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 367 records from QLD DERM Coastal Bird Atlas (Trial). 51546 records from SPSF - Herbário Dom Bento José Pickel. 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1872 records from Herbier National de Guinée (HNG) (BID-AF2015-0066-REG). 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 2 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 6071 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 4036949 records from Natural History Museum (London) Collection Specimens. 7 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 1 records from A new genus and new species assigned to Macrophthalmidae (Decapoda: Brachyura: Thoracotremata) from the Ryukyu Islands, Japan. 6 records from Six new and one known species of Geomonhystera (Nematoda, Monhysteridae) from moss, an epiphytic plant and soil in México and Ecuador. 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 2532 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 16128 records from Colección Ictiológica del Instituto Alexander von Humboldt. 33 records from The Gomphocerinae Tarbinsky, 1932 (Orthoptera: Acrididae) fauna of the Turkish Thrace. 7 records from Two new species of Quichuana Knab (Diptera: Syrphidae) from the paramo ecosystems in Colombia. 139695 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 1510 records from Collection botanique Jaubert et Saul (BOUM). 4546 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 1 records from Pelops tardus. 86 records from Modelación de la distribución real y potencial de especies de dos géneros de Mimosoideae: Mimosa y Prosopis (Leguminosae) en México. 90 records from NZCS Sipaliwini Savanna Expeditions 1997/2014. 4 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 15754 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 616 records from ENBI WP 13 Martius C. F. P. von Collection subset (Muenchen). 2568 records from Fish (NHMK-PI). 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 174 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 3 records from Two new species of Polana (Hemiptera: Cicadellidae: Iassinae: Gyponini) and redescription of Polana (Striapona) desela. 2 records from Marthamea bayae, a new species of stonefly from Algeria (Plecoptera: Perlidae). 33 records from The catshark genus Scyliorhinus (Chondrichthyes: Carcharhiniformes: Scyliorhinidae): taxonomy, morphology and distribution. 2 records from Schizopyga alinae, a genus of pimpline parasitoid wasps (Hymenoptera: Ichneumonidae: Pimplinae) new to the Afrotropical region. 34 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 2 records from A new record of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from Northern Vietnam with description of two new species. 9102 records from The Fungal Collection at the Botanische Staatssammlung München. 48 records from Calvariopsis gen. nov., a new genus of Neotropical Scirtidae (Coleoptera: Scirtoidea). 1030627 records from Phanerogamic Botanical Collections (S). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Phylogeny of Bathysciotina Guéorguiev, 1974, based on morphology with a special emphasis to Italian genera and with the description of a new species of Halbherria (Coleoptera Leiodidae Cholevinae Leptodirini). 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 47 records from A study on the genus Stenus Latreille from Zhuji City of Zhejiang, East China (Coleoptera, Staphylinidae). 19175 records from Herbarium specimens of Hokkaido University Museum. 4 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 174 records from Lichen specimens of Okinawa Prefectural Museum & Art Museum. 15 records from Caridina malanda, a new species of freshwater shrimp (Crustacea: Decapoda Atyidae) from the Wet Tropics World Heritage area, north-eastern Queensland Australia. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 488 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A new species of Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae; Conocephalinae; Copiphorini) from India. 3 records from New species of Lonchaeidae (Diptera) from Switzerland and Serbia with arevised checklist of the Swiss fauna. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 1 records from Papilio Sticheli nov. spec. aut subsp.. 2 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 73 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ben Hell. 307 records from Revision of the genus Platyscelis Latreille, 1818 from China (Coleoptera: Tenebrionidae: Platyscelidini). 32 records from Australian Marsh Beetles (Coleoptera: Scirtidae). 9. The relations of Australasian Ypsiloncyphon species to their Asian congeners, additions, mainly to Petrocyphon and Prionocyphon, and a key to Australian genera of Scirtinae. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 1 records from Callogorgia lucaya sp. nov., a new species of deep-sea Primnoidae (Anthozoa: Octocorallia) from the western Atlantic. 871 records from FLORA REGIONAL Y OTROS PAÍSES. MMHNSR 2018. 19 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 23 records from Many things come in small packages: Revision of the clawless geckos (Crenadactylus: Diplodactylidae) of Australia. 10 records from Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 110 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 34 records from ZUEC-EPH - Coleção de Ephemeroptera do Museu de Zoologia da UNICAMP. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 12 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 346 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 15 records from A new genus and four new species of subfamily Cyclocypridinae (Crustacea, Ostracoda) from Thailand. 4 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 44 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 3 records from A new species of the genus Gracixalus (Amphibia: Anura: Rhacophoridae) from Mount Jinggang, southeastern China. 8 records from Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae). 30 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 46057 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 15 records from Redescription of the Indo-West Pacific scorpionfish Scorpaena neglecta Temminck & Schlegel, 1843, a senior synonym of four nominal species (Teleostei: Scorpaenidae). 1 records from Nothrus pigerrimus. 79 records from Catalogue of the Syrphidae of Egypt (Diptera). 231092 records from UF FLMNH Ichthyology. 1 records from New record of the genus Bambusiphaga (Hemiptera: Delphacidae: Tropidocephalini) from India with description of a new species. 2 records from Descripción de una nueva especie del grupo Drosophila tripunctata (Diptera: Drosophilidae) en Cruz Loma, Pichincha, Ecuador. 33 records from Two new species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) from Brazilian caves. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 2 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica). 33 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 18224 records from K-State Museum of Entomological and Prairie Arthropod Research. 7 records from A new species of Dwarf Japalura sensu lato (Reptilia: Squamata: Agamidae) from the upper Mekong River in Eastern Tibet, China, with notes on morphological variation, distribution, and conservation of two congeners along the same river. 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 62210 records from Tiroler Landesmuseum Ferdinandeum. 89 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 9 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1 records from A new species of the genus Comaroma in China (Araneae: Anapidae). 5 records from Evaluación de la situación de Tillandsia mauryana en el Apéndice II de la CITES, según su estado de conservación y comercio. 78 records from Mammals (GNHM-MM). 3 records from The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species. 2 records from Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae). 102 records from Twenty new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental Region. 158 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 9 records from Description of a new genus and species of Chrysopetalidae (Annelida: Polychaeta) from the NE Atlantic, with some further records of related species. 2 records from On the taxonomic status of amphidromous shrimp Paratya borealis Volk, 1938 (Crustacea: Decapoda: Atyidae) from the south of the Russian Far East. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 942 records from New data on the dragonfly fauna of the Moulouya River Basin and the Oriental Region, Morocco (Odonata). 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 1352 records from Studies on the Australian Muscidae (Diptera). VIII. The genus Lispe Latreille, 1797. 2 records from Youngest representative of the extinct genus Microphorites in the Eocene amber of France (Diptera: Dolichopodidae: Microphorinae). 13 records from An annotated species list of regular echinoids from Sri Lanka with notes on some rarely seen temnopleurids. 5 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) from northwestern Vietnam. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 64 records from The congrid eel genus Ariosoma in Taiwan (Anguilliformes: Congridae), with description of a new species. 1127 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Taiwan, with keys to all 13 species of the Simulium varicorne species-group. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 24795 records from Université d'Aix-Marseille. 34 records from Taxonomic review of Athliini (Coleoptera: Scarabaeidae: Melolonthinae), a new tribe of scarab beetles endemic to South America. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1 records from Murcia trimaculata. 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 36 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 142 records from Three new species, Elathous zagrosensis sp. n., Zorochros dilatatus sp. n., and Dicronychus iranicus sp. n., and noteworthy records of click beetles from western Iran (Coleoptera: Elateridae). 3 records from An annotated checklist of the psyllids of New Zealand (Hemiptera: Psylloidea). 2 records from A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Cu Lao Cham Islands, central Vietnam. 23 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 87 records from Barsura Volynkin, Dubatolov & Kishida, gen. nov., with descriptions of three new species (Lepidoptera, Erebidae, Arctiinae). 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 9636 records from Herpetology. 2401 records from UWYMV Bird Collection (Arctos). 11994 records from Hatikka Observation Database. 24 records from A new species of Bedotia (Teleostei: Atherinomorpha: Bedotiidae) from the Rianila drainage of Eastern Madagascar, with redescriptions of Bedotia madagascariensis and Bedotia geayi.. 2 records from A new groundwater-dwelling species of Euryrhynchina from Cameroon (Malacostraca, Decapoda, Euryrhynchidae). 2088 records from OSAC North American Cossoidea -beta version. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 23 records from A survey of East Palaearctic Gnaphosidae (Araneae). 5. On Synaphosus from Central Asia. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2020 records from Birds (NHMK-BI). 6717 records from LSUMZ Mammal Tissues. 284 records from Banco de Germoplasma Vegetal del Jardín Botánico de Olarizu (Vitoria-Gasteiz)/Olarizuko Lorategi Botanikoaren Landare Germoplasma Bankua (Vitoria-Gasteiz). 5 records from A new species of Acanthosaura Gray 1831 (Reptilia: Agamidae) from central Vietnam. 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 4 records from Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 4 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 5780 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 11098 records from Herbario de Universidad de Murcia: MUB. 524 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 3 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 37 records from Checklist of decapods (Crustacea) from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: I. Infraorder Caridea: families Hippolytidae, Lysmatidae, Ogyrididae, Processidae and Thoridae. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 32916 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 2989 records from Sponge collection of National Museum of Nature and Science. 20 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 554 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 7638 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 373028 records from South Australian Museum Australia provider for OZCAM. 1 records from A new species of Tapiena (Orthoptera: Tettigonioidea: Phaneropterinae) from Brunei Darussalam (Borneo, Southeast Asia). 6 records from New anaxyelids (Hymenoptera: Anaxyelidae) from the Cretaceous of Asia. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 3 records from A new species of forest-dwelling Cyrtodactylus Gray (Squamata: Gekkonidae) from the Indawgyi Wildlife Sanctuary, Kachin State, Myanmar. 1261 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 2100 records from Colección de Polypodiales, Proteales, Psilotales y Ranunculales del Museo Botánico CORD - IMBIV. 100 records from Brock University Herbarium (BU). 148 records from Herbarium BSG Hepaticopsida. 10 records from Arachnid specimens of Okinawa Prefectural Museum & Art Museum. 22 records from Descriptions of eight new species of the genus Parancistrocerus Bequaert (Hymenoptera: Vespidae: Eumeninae), with a key to the Oriental species. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 16488 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc). 26 records from Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China. 1040 records from Invasive Alien plant species of Malawi. 18 records from Colaphellus palaestinus Achard, a new leaf-beetle for Europe (Coleoptera, Chrysomelidae, Chrysomelinae). 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 4 records from Redescription of Alopecosa albostriata (Araneae: Lycosidae) based on specimens from Siberia. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 79 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 22 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 85 records from Benthic Polychaeta (Annelida) from La Paz Bay and Southwestern Gulf of California. 2039 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 6491 records from Les Rubiaceae, Orchidaceae, Moraceae, Sapindaceae, Malvaceae, Melastomataceae, Verbenaceae, Loganiaceae, Sapotaceae, Scrophulariaceae, Sterculiaceae, Liliaceae, Meliaceae, Ochnaceae, Tiliaceae, Rosaceae, Solanaceae, Violaceae, Zingiberaceae, Myrtaceae, Rutaceae, Loranthaceae et quelques 71 autres familles de plantes de l'Herbier du Centre National de Floristique en Côte d'Ivoire.. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 5 records from Troglocaris (Xiphocaridinella) kumistavi sp. nov., a new species of stygobiotic atyid shrimp (Crustacea: Decapoda: Atyidae) from Kumistavi Cave, Imereti, Western Georgia, Caucasus. 3 records from Cylindroniscus platoi (Isopoda: Oniscidea: Styloniscidae), a new cave-dwelling species from Lagoa Santa Karst, Southeastern Brazil. 280 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 372 records from Colección de Entomología - Arthropoda. 152102 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40177 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 15 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 887 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 21696 records from Fish specimens of Bihoro Museum. 3627 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 462 records from Collection Lepidoptera SMF. 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 24 records from Schismatothelinae spiders (Araneae, Mygalomorphae, Theraphosidae) from Colombia: four new species and an approach to their diversity. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Description of a new Kempnyia Klapálek from Brazil (Plecoptera: Perlidae) with life stages associated using DNA barcodes. 2799 records from University of Sindh Jamshoro Herbarium. 64 records from Review of Poecilimon species with inflated pronotum: description of four new taxa within an acoustically diverse group. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 28 records from The Apseudomorpha (Crustacea: Tanaidacea) of the Gulf of Cadiz and Horseshoe Continental Rise (NE Atlantic): A taxonomic review with new records, species, and ecological data. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 1 records from The mature larva and pupa of Tychius subsulcatus Tournier, 1847 (Coleoptera, Curculionidae), with comments on its biology and phylogenetic relationships. 7 records from Three new species of phytoseiid mites (Acari: Phytoseiidae) from Bahia State, Brazil. 25 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 6 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 21 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 2 records from A contribution to the systematics of Salea anamallayana (Beddome, 1878) and S. horsfieldii Gray, 1845 (Squamata: Agamidae: Draconinae). 3367 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 9 records from First record and new species of the Oriental leafhopper genus Trifida Thapa & Sohi (Hemiptera: Cicadellidae: Typhlocybinae) from China. 1 records from New species and new record of Thraulodes Ulmer, 1920 (Ephemeroptera: Leptophlebiidae: Atalophlebiinae) from Brazil. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 39 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 182 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 13 records from Towards the taxonomy of Corynoneura Winnertz (Diptera: Chironomidae: Orthocladiinae) from the Russian Far East and Eastern Siberia. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 204 records from Echinoderms from the Seaflower Biosphere Reserve. 1 records from A new species of hydrothermal vent stalked barnacle Vulcanolepas (Scalpelliforms: Eolepadidae) from the North Fiji Basin, Southwestern Pacific Ocean. 1994 records from EVB herbarium - Herbário Evaldo Buttura - Herbário Virtual REFLORA. 1 records from Celaeno obsoleta. 25 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 283430 records from Allan Herbarium (CHR). 254268 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 2 records from Four palaeonemerteans (Nemertea: Anopla) from a tidal flat in middle Honshu, Japan. 3 records from Miltochrista wangmini, a new species from China (Lepidoptera, Erebidae, Arctiinae). 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 7 records from A novel member of the Hemidactylus brookii complex (Squamata: Gekkonidae) from the Western Ghats of Maharashtra, India. 3984 records from Fungal Collection of Natural History Museum and Institute, Chiba. 14275 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 35 records from Review of the genus Typhloiulus Latzel, 1884 in the Dinaric region, with a description of four new species and the first description of the male of Typhloiulus insularis Strasser, 1938 (Diplopoda: Julida: Julidae). 7 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 18567 records from Cercle des mycologues de Montréal Fungarium (CMMF). 27 records from New records in vascular plants alien to Kyrgyzstan. 3 records from Aquatic microdrile Oligochaeta (Annelida, Clitellata): New nominal taxa and combinations since 1984. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 1 records from A new genus and species of congrid eel from the Philippines (Anguillliformes: Congridae: Bathymyrinae). 77258 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 233 records from Colección Mastozoológica Universidad de los Llanos. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 16 records from Mascarapion, a new genus of the Apioninae (Coleoptera, Curculionoidea) from the Mascarene Islands. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 28109 records from Marie-Victorin Herbarium (MT) - Bryophytes. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 67 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 70 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 1 records from First record of the cicadas genus Orientopsaltria Kato, 1944 (Hemiptera: Cicadidae) from Vietnam, with description of one new species. 17 records from Three new species of genus Mecopoda Serville, 1831 from China (Orthoptera: Tettigoniidae: Mecopodinae). 11 records from Nematomorpha from Hong Kong and description of a new species from Malaysia. 2 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 9 records from The genus Jeekelosoma Mauriès, 1985 - Moroccan cave millipedes (Diplopoda, Polydesmida, Paradoxosomatidae). 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 181 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 96726 records from Buffalo Society of Natural Sciences Clinton Herbarium. 1 records from Schistobrachia kabata sp. nov. (Siphonostomatoida: Lernaeopodidae) from rajiform hosts off South Africa. 3239 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 2 records from Trachelus stipa (Hymenoptera: Cephidae), a new stem sawfly from Central Anatolia associated with feather grass (Stipa holosericea, Poaceae). 4 records from The identity of Osteobrama cotio, and the status of “ Osteobrama serrata ” (Teleostei: Cyprinidae: Cyprininae). 3185 records from Utah State University, Intermountain Herbarium. 64 records from Revision of the Barsine cardinalis - anomala ' species-complex' (Lepidoptera, Erebidae, Arctiinae). 866 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 45 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 247828 records from CAS Entomology (ENT). 39614 records from Naturalis Biodiversity Center (NL) - Pisces. 54 records from Molluscan fauna of Gueishan Island of Taiwan. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 34 records from Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species. 2968 records from John Clayton's Fijian Moth Collection. 2166 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 87 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 2970 records from Data mobilized by the National Herbarium of Benin in the framework of the JRS Biodiversity project of Benin. 320 records from Myxomycetes collection of the University of Eastern Finland. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 70 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 2389 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 299 records from Insect Ichneumon fly (KIDR-IN). 47 records from A taxonomic revision of the genus Sirthenea (Hemiptera: Heteroptera: Reduviidae) of the Old World. 338 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 1 records from Enlarging the monotypic Monocarpieae (Annonaceae, Malmeoideae): recognition of a second genus from Vietnam informed by morphology and molecular phylogenetics. 3 records from A new species of sponge-dwelling Elacatinus (Pisces: Gobiidae) from the western Caribbean.. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 14009 records from Collection Trichoptera - SMF. 49078 records from Insect specimens of Tochigi Prefectural Museum. 3161 records from Lichenized fungi of Vietnam (PHH Herbarium, Cryptogam collection). 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 107 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 235 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 3 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 10 records from Supplement to the knowledge of the genus Batraxis Reitter (Coleoptera: Staphylinidae: Pselaphinae) of China. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 107285 records from Arizona State University Hasbrouck Insect Collection. 21 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 429 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 229986 records from Vascular plant herbarium TRH, NTNU University Museum. 3381 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 6 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 76 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 16 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 41 records from Registros Primates Neotropicales Convocatoria APC. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 760 records from Arthropoda specimens of Toyama Science Museum. 4 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 4 records from Two new species of Atlantoscia Ferrara & Taiti, 1981 (Isopoda: Oniscidea: Philosciidae) from southern Brazil described in the light of integrative taxonomy. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 11 records from Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae). 4 records from Flightless Catapionus (Coleoptera: Curculionidae: Entiminae) in Southwest China survive the Holocene trapped on mountaintops: new species, unknown phylogeny and clogging taxonomy. 150 records from Collection des données de biodiversité marine de Polynésie française - IRD Nouvelle-Calédonie. 6 records from Systematics of New Guinea treefrogs (Litoria: Pelodryadidae) with erectile rostral spikes: an extended description of Litoria pronimia and a new species from the Foja Mountains. 7 records from A name for the nurse-frog (Allobates, Aromobatidae) of Floresta Nacional de Carajás, Eastern Brazilian Amazonia. 5 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 33 records from Systematic revision of Central American Calligrapha Chevrolat of the subgenus Erythrographa subgen. nov. (Coleoptera: Chrysomelidae, Chrysomelinae). 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 7128 records from La familia Asclepiadaceae en México. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 1 records from On two new synonyms of the orb-weaving spider Orsinome vethi (Hasselt, 1882) (Araneae, Tetragnathidae). 4 records from New species of Raphidascaris (Sprentascaris) (Nematoda: Anisakidae) in Rineloricaria steinbachi (Actinopterygii: Loricariidae) from Northwest Argentina. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 54 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 7 records from A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911. 200162 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 795 records from Histoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 6 records from Description of the Nymph of Tramea binotata (Rambur, 1842) (Odonata: Libellulidae). 6197 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 16 records from The Stenus cirrus group (Coleoptera, Staphylinidae) in Fujian, East China. 54 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 45 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 65970 records from Mammals Specimens. 36 records from SIM-XII Jornadas Micológicas El Ilustre Minero. 2 records from Two new species of the genus Metaxonchium Coomans & Nair, 1975 (Nematoda, Dorylaimida, Belondiridae) from Vietnam. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 501 records from Lauri Mällo private collection of Lepidoptera. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 2 records from A new species and new record of Polycystididae (Rhabdocoela: Kalyptorhynchia) from China. 30004 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 107 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 50 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 24 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 24 records from Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic. 4400 records from USAC Mammals Collection. 4299 records from New Zealand Biodiversity Recording Network. 3 records from A new species of the genus Colilodion Besuchet, 1991 (Coleoptera: Staphylinidae: Pselaphinae) from Mindanao, the Philippines. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 3 records from Description of the mature larva of Austrolimnius nyctelioides (Germain, 1892) and A. elatus Hinton, 1941 (Coleoptera: Elmidae). 1 records from The tenth member of stout newt (Amphibia: Salamandridae: Pachytriton): Description of a new species from Guangdong, southern China. 3652 records from Museu Paraense Emílio Goeldi - Paleoinvertebrate Collection. 7075 records from SMNS Herpetologie. 5 records from Redescription of a little-known spider species, Mesiotelus lubricus (Simon, 1880) (Aranei: Liocranidae) from China. 4 records from A new species of Ergasilus von Nordmann, 1832 (Copepoda: Cyclopoida) from the gills of a dasyatid ray, Himantura oxyrhyncha (Sauvage, 1878) from West Kalimantan, Indonesia. 93 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 2068 records from Colección Zoológica de la Universidad del Tolima (CZUT)-Anfibios. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 42570 records from Bird Collection of Museum and Institute of Zoology PAS. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 2 records from Solving a nomenclatural conundrum: Cernosvitovia crainensis (Mršić, 1989) and Aporrectodea macvensis Šapkarev in Mršić, 1991 (Lumbricidae). 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 1 records from Lissotes working-group. 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 6 records from Two new species of the genus Gibbotettix Zheng, 1992 (Orthoptera: Tetrigidae, Cladonotinae) from China. 14 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 38 records from Visual Plants (144.41.33.158) - Plants from Costa Rica, illustrations by Teresa Barantes Lobo. 5640 records from Collection Echinodermata SMF. 45 records from Robert Forsyth Terrestrial Gastropods Collection. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5020 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 10 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 2 records from A new species of the ghost shrimp genus Neocallichirus Sakai, 1988 from Iran, and new record of N. manningi Kazmi & Kazmi, 1992 (Decapoda: Axiidea: Callianassidae). 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 46074 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 240 records from Taxonomy and natural history of the myrmecophilous genus Clinterocera Motschulsky, 1858 (Coleoptera: Scarabaeidae: Cetoniinae) from China and adjacent regions: revision of the C. jucunda species group. 1 records from On the Chilopoda from Turkey. 124 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 4 records from A new species of the remarkable brittle star genus Astrophiura (Echinodermata: Ophiuroidea) from the western Atlantic Ocean. 1 records from A new species and a new record of Horaeomorphus Schaufuss (Staphylinidae: Scydmaeninae: Glandulariini) from China. 6 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 3781 records from VMNH SVDM Vertebrate Paleontology. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 16 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 42 records from Contribution to the knowledge of the earthworm fauna of Turkey with description of three new species (Clitellata: Megadrili). 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 1 records from Description of a new species of the genus Mongolotettix Rehn, 1928 (Orthoptera: Acrididae) from Fujian, China. 150 records from Estudio de la variabilidad genética de Fundulus lima y sus relaciones filogeográficas con otros fundúlidos (Pisces: Fundulidae) de la Península de Baja California, México. 5 records from Paraneseuthia Franz of Japan: two new species and rediscovery of the enigmatic P. holzneri Franz (Coleoptera, Staphylinidae, Scydmaeninae). 847 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 3689 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 83 records from Taxonomic study of the genus Hypatopa Walsingham, 1907 (Lepidoptera: Blastobasidae) in China, with descriptions of five new species. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 5 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from Arthropoden aus südostalpinen Höhlen.. 25 records from Taxonomic revision of Plyomydas Wilcox & Papavero, 1971 with the description of two new species and its transfer to Mydinae (Insecta: Diptera: Mydidae). 289 records from bmhs_butterfly_collection. 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 4 records from A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan. 7 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 3 records from A new Antillobisium species (Arachnida: Pseudoscorpiones: Bochicidae) from Cuba, with biogeographical and ecological remarks on the genus. 3 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 84 records from A revision of the spider genus Raveniola (Araneae, Nemesiidae). I. Species from Western Asia. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 104 records from Mammalogie ZMK. 10 records from Checklist of the Free-Living Marine Nematodes of the Iberian Peninsula (north east Atlantic). 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 2063 records from Flora d'Andorra. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 4 records from Four new earthworm species of Kazimierzus Plisko, 2006 (Clitellata, Kazimierzidae). 6010 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 15 records from Conringia orientalis. 5 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 11 records from A new genus and three new species of nemacheilid loaches from northern Irrawaddy drainage, Myanmar (Teleostei: Cypriniformes). 1 records from Erpetogomphus oxybelis sp. nov. from Veracruz, Mexico (Odonata: Gomphidae). 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 1 records from A new species of the genus Paratus Simon (Araneae: Liocranidae) from Thailand. 1976 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 9 records from Discovery of the genus Pseudepione Inoue, 1943 in Taiwan, with description of a new species (Lepidoptera: Geometridae: Ennominae). 6 records from On the new monotypic wolf spider genus Ovia gen. nov. (Araneae: Lycosidae, Lycosinae). 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 2289 records from Specimen records of spiders (Arachnida: Araneae) by monthly census for 3 years in forest areas of Yakushima Island, Japan. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 7873 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 738 records from Correlación entre las condiciones ambientales y la pesquería de anchoveta a lo largo de la costa de Baja California. 6566 records from CABI Lepidoptera Collection. 13 records from Two new and potentially highly threatened Megophrys Horned frogs (Amphibia: Megophryidae) from Indochina’s highest mountains. 4 records from Two remakable new species of Notocera Amyot and Serville, 1843 (Hemiptera, Membracidae, Hypsoprorini) from the Brazilian Caatinga. 124062 records from University of Guelph Insect Collection (DEBU). 2 records from Two new species of Sympagella (Porifera: Hexactinellida: Rossellidae) collected from the Clarion-Clipperton Zone, East Pacific. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 3131 records from Solitary bees collected in a large-scale field experiment in power line clearings, southeast Norway. 1 records from Revision and redefinition of the crematogastrine ant genus Tetheamyrma BOLTON, 1991, with the description of a new species and the first description of the dealate queen (Hymenoptera: Formicidae). 14 records from Redescription and new records of a poorly known leucosiid crab, Pseudophilyra punctulata Chen & Ng, 2003, and description of a new species of Pseudophilyra from Japan (Crustacea: Decapoda: Brachyura). 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 809 records from ant-plant_symbioses. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 30 records from New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan. 29 records from Herbarium Senckenbergianum (FR) - Protista. 837 records from Colección de Zoología Invertebrados - Carcinología. 1 records from New earthworm records (Clitellata: Lumbricidae) from Bulgaria since 2012. 3 records from Zoology in the Middle East. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 3947 records from Herbario del Jardín Botánico-Histórico La Concepción: HBC. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 28 records from Checklist of the freshwater snails (Mollusca: Gastropoda) of Mongolia. 86 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 16 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 32 records from The soft ticks (Parasitiformes: Ixodida: Argasidae) of Mexico: species, hosts, and geographical distribution. 2000 records from Mollusk Collection of Yokosuka City Museum. 1139 records from SWECO. 2321 records from Dataset of fungus gnats (Diptera,Sciaroidea) from Møre og Romsdal county in Norway. 60887 records from EAC - Herbário Prisco Bezerra. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 8006 records from Knerer collection / Gschwendtner property. 1 records from Description of a new neotropical species of Xiqilliba Kramer (Hemiptera: Cicadellidae: Neocoelidiinae). 30213 records from Collection Crustacea - ZMB. 2 records from Ceraphron krogmanni (Hymenoptera: Ceraphronidae), a new species from Lower Saxony with unusual male genitalia. 3 records from New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon. 726 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 1200 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 6 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from The polyps of Oceania armata identified by DNA barcoding (Cnidaria, Hydrozoa). 4 records from On Starengovia Snegovaya, a genus of Asian nemastomatines (Arachnida: Opiliones: Nemastomatidae). 1 records from Myriopoden von Epirus. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 1397 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 154 records from Dermaptera in the icipe collection. 1 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 17 records from Systematics of the New Zealand Weevil Etheophanus Broun (Curculionidae: Molytinae). 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 14953 records from MVZ Egg and Nest Collection (Arctos). 73 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 18 records from Overvåking Røsskleiva NR. 11 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 1002 records from Herbario HUAZ Enrique Forero. 6 records from Coendutermes tucum Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and additional notes. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 2 records from Four new generic and 14 new specific synonymies in Pholcidae, and transfer of Pholcoides Roewer to Filistatidae (Araneae). 1 records from Redescription of Parafronurus youi and generic affinities (Ephemeroptera, Heptageniidae, Ecdyonurinae). 333 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 91739 records from E. C. Smith Herbarium (ACAD). 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 167 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 173 records from Colección del Museo de Ciencias Naturales “José Lorca”. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 72 records from Base de datos de Rana catesbeiana.. 5 records from Taxonomic revision of Saffron-billed Sparrow Arremon flavirostris Swainson, 1838 (Aves: Passerellidae) with comments on its holotype and type locality. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 111 records from A taxonomic revision of Globba subsect. Nudae (Zingiberaceae). 53 records from New data on the taxonomy, distribution and host plants of Australian Epermeniidae (Lepidoptera: Epermenioidea). 62 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 1808 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 111 records from The bees (Hymenoptera: Apoidea) of the Maltese Islands. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 1821 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 17 records from Further information on Lolibaia Gorbunov & Gurko, 2017 (Lepidoptera: Sesiidae: Synanthedonini) with description of three new species from tropical Africa. 1 records from Addendum to MANFRED R. ULITZKA (2019) Five new species of Rohrthrips (Thysanoptera: Rohrthripidae) from Burmese amber, and the evolution of Tubulifera wings. Zootaxa, 4585: 027 - 040.. 55 records from Pyura (Tunicata: Ascidiacea: Pyuridae) on the coasts of Panama. 10 records from Description of the larval stages of the Shield Darter, Percina peltata (Pisces: Percidae), in New York.. 1 records from Fort Hays State University Sternberg Museum of Natural History - Vertebrate. 17825 records from Duke University. 836473 records from Museums Victoria provider for OZCAM. 6859 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 21 records from Trichromothrips genus-group (Thysanoptera, Thripidae) from China, with descriptions of three new species and ten new records. 215195 records from SysTax - Zoological Collections. 9 records from Epimeria cleo sp. nov., a new crested amphipod from the Ross Sea, Antarctica, with notes on its phylogenetic affinities (Crustacea, Amphipoda, Eusiroidea, Epimeriidae). 2 records from A new amphibious troglobitic styloniscid from Brazil (Isopoda, Oniscidea, Synocheta). 2 records from A new species of the stenopodidean shrimp genus Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Ryukyu Islands, Indo-West Pacific. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 2 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 1 records from A new species of nurse-frog (Aromobatidae, Allobates) from the Madeira River basin with a small geographic range. 26 records from Three new species of Thaloe Brescovit (Araneae: Anyphaenidae: Anyphaeninae), with descriptions of the first known females of the genus. 71 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 877 records from Sphaeriid clams. 348 records from Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 350 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 735736 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 4 records from Gammaropsis elvirae sp. nov., a widely distributed amphipod (Amphipoda: Photidae) in the Yucatan Shelf, with ecological comments and a key for the genus in tropical America. 187 records from UWIZM Mammals. 48 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 2845 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 8 records from Discovery of leaf-mining Tischeriidae (Lepidoptera) in Colombia and their distribution in the Neotropics. 9 records from Oxynoemacheilus kentritensis, a new species from the upper Tigris drainage in Turkey with remarks on O. frenatus (Teleostei: Nemacheilidae). 16 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28408 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 35 records from Three new species of Mesovelia Mulsant & Rey (Hemiptera: Heteroptera: Mesoveliidae) from India. 534 records from MEXU/Tipos de plantas vasculares. 56 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 8 records from Macropsini (Hemiptera: Cicadellidae) of Thailand, with description of two new species and three new country records. 8 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 1613 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 13 records from First record of Africactenus Hyatt, 1954 and redescriptions of two poorly known species of Ctenus Walckenaer, 1805 (Araneae, Ctenidae, Cteninae) from India. 134 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 7 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 1 records from The current status of Neocnus Arredondo, 1961 (Mammalia: Edentata: Pilosa: Megalonichidae) and a replacement name for its junior homonym in the sea cucumber family Cucumariidae (Echinodermata: Holothuroidea: Dendrochirotida: Cucumariidae). 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 6 records from Zanna robusticephalica sp. nov. (Hemiptera: Fulgoromorpha: Fulgoridae) from China, with comments on some ultrastructural characters of the new species. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 5 records from One new Pseudopoda species group (Araneae: Sparassidae) from Yunnan Province, China, with description of three new species. 7 records from A new genus and species of a terrestrial cavernicolan planarian from Barro Colorado Island, Panama (Platyhelminthes, Tricladida, Cavernicola). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 112603 records from Herbarium Willing at Herbarium Berolinense, Berlin (B). 1057 records from Hongos ectomicorrizógenos y myxomycetes asociados con Picea chihuahuana en la Sierra Tarahumara. 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 127 records from New species, redescriptions and phylogenetic revision of tribe Dacini (Diptera: Tephritidae: Dacinae) from India based on morphological characters. 1716 records from KTU Pinophyta. 5 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 480 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 1 records from A new species of Parafimbrios from northern Vietnam (Squamata: Xenodermatidae). 2126 records from Dolichopodidae of Portugal - dataset 2009-2018. 1915 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 9304 records from Echinoderm collection of National Museum of Nature and Science. 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 30535 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 25 records from Mantidflies (Neuroptera, Mantispidae) from Tocantins state (Brazil): distribution and identification key. 915278 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 64 records from Chenopodium vulvaria. 19 records from Review of the genus Trichactia Stein (Diptera: Tachinidae) in the Palaearctic Region, with the description of a new species from Iran and the East Mediterranean. 17713 records from NCSM Mammals Collection. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 4 records from A new species of Selatosomus Stephens and the occurrence of Pristilophus melancholicus (Fabricius) in China (Coleoptera: Elateridae: Dendrometrinae). 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 20027 records from Coleção de Porifera do Museu Nacional - UFRJ. 3951 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Osteological. 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 4 records from Two new cavernicolous Pselaphinae (Coleoptera: Staphylinidae) from southern China. 1 records from On the Chilopoda from Turkey. 10552 records from Insect specimens of Toyota City Nature Sanctuary. 7 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 124 records from Lepidoptera Pollinators from National Museum of Tanzania collection. 20 records from Pelagic ctenophores from the São Sebastião Channel, southeastern Brazil. 4207 records from CASES2003_2004. 6 records from Taxonomy and biology of Simulium clarkei Stone & Snoddy (Diptera: Simuliidae), a poorly known black fly of the southeastern United States. 124 records from North Marine Region whaler shark collection records (DEW collation), Australia (1999- 2005). 3 records from Nouvelles fourmis de Madagascar.. 376 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 570 records from Flora ficológica marina de Tamaulipas. 151 records from CHAS Botany Collection (Arctos). 38004 records from Vascular plants collection of Hiratsuka City Museum. 39 records from A photographic catalog of Ceraphronoidea types at the Muséum national d’Histoire naturelle, Paris (MNHN), with comments on unpublished notes from Paul Dessart. 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 3006 records from Plantas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 386 records from Mammal specimens of Kawasaki Municipal Science Museum. 12 records from A new genus of nesticid spiders from western European Peninsulas (Araneae, Nesticidae). 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 17 records from A new species of Laurenceomyia Wagner & Stuckenberg, with a key to species and new records for Psychodidae (Diptera) from Uruguay. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 13 records from Visual Plants (144.41.33.158) - Private collection of Florian Werner. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 1 records from Carabodes coriaceus. 7814 records from Odonata de Veracruz. 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 1 records from Two new species of earthworms belonging to the genus Amynthas (Oligochaeta: Megascolecidae) from Guangxi Province, China. 1 records from Review of the genus Suwallia (Plecoptera: Chloroperlidae) from China with description of Suwallia jihuae sp. nov. from Sichuan Province. 19 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2 records from A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species. 18 records from The genus Ranatra Fabricius (Heteroptera: Nepidae) in Borneo, with a redescription of Ranatra spinifrons Montandon and the description of a new species. 2 records from A new species of black fly with a yellow thorax in the genus Prosimulium (Diptera: Simuliidae) in Japan. 3 records from New findings of Hexalona-branch representatives in Brazil, with a description of Prenda gen. nov. (Crustacea: Anomopoda: Aloninae). 7 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 19021 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 22 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 11 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 1260 records from A Catalogue and Historical Study of the Odonata of Ecuador. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 99 records from Ant-like stone beetles on the roof of the world. Cephenniini of Nepal and Bhutan (Coleoptera, Staphylinidae, Scydmaeninae). 30 records from On the taxonomy of the genera Planovalvata Dubatolov & Kishida, Stigmatophora Staudinger and Pseudomiltochrista Dubatolov & Bucsek, with description of one new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 4991 records from SYKO Herbarium Mosses Collection. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 3 records from A new fossil species of Pycnomerus Erichson (Coleoptera: Zopheridae) from Baltic amber, and a replacement name for a Recent North American congener. 6 records from New data on the distribution of aquatic bugs (Hemiptera) from eastern Morocco with notes on chorology. 27 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 5 records from Loricifera - SMF. 100970 records from Canadian Museum of Nature Bird Collection. 36 records from On brachypterous phaneropterine katydids (Orthoptera: Tettigoniidae: Phaneropterinae) from the Iguaçu National Park, Brazil: three new species, new record and bioacoustics. 5 records from New taxa and notes of katydids from the tribe Meconematini (Orthoptera: Meconematinae) from Brunei Darussalam (Part 2). 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 3 records from Cyrtodesmus baerti, n. sp., a cryptic millipede from the Galápagos Islands, Ecuador (Diplopoda, Polydesmida, Cyrtodesmidae). 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 1 records from Orthochaetes estrelanus sp. n., a new species from northern Portugal and new records of other Styphlini (Coleoptera, Curculionidae).. 5 records from Three new species of Lyssomanes HENTZ, 1845 from Peru (Arachnida: Araneae: Salticidae). 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 3 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 196 records from Collection des mammifères d'Auvergne. 12 records from An annotated checklist of the earthworm fauna of Turkey (Oligochaeta: Lumbricidae). 500 records from Plant specimens of Oiso Municipal Museum. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 2130 records from database_hemiptera. 43 records from bmhs_beetle_collection. 53 records from Unraveling Ocyptamus and the Baccha legacy (Diptera: Syrphidae): redefinition of groups and new species descriptions. 25 records from Morphologische Daten von Natrix. 7 records from Taxonomic revision of the epigean representatives of the spider subfamily Harpacteinae (Araneae: Dysderidae) on the island of Crete. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 12645 records from Brown University Herbarium. 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 200651 records from Mississippi Entomological Museum. 277 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 9 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 8 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 98 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 218 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 148 records from BioAcoustica: Wildlife Sounds Database. 40 records from Records of Giant Silkmoths (Saturniinae) from Vermont Collections and 2002-2007. 5 records from A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia). 197 records from TransForest - vegetation, lichen and fungi data 2016. 21 records from Studies in Guatemalan Ensifera: New Glaphyrosoma species (Orthoptera: Anostostomatidae) and additional data for other described species. 7 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 2 records from A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 3 records from Callianassa ehsani, a new species of Callianassidae (Crustacea, Decapoda, Axiidea) from Gulf of Oman, Iran. 1 records from Gymnesigobius medits (Teleostei: Gobiidae), a new gobiid genus and species from the western Mediterranean slope bottoms. 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 2522 records from NMU Mammal Collection (Arctos). 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 3 records from Species diversity of Rhinebothrium Linton, 1890 (Eucestoda: Rhinebothriidea) from Styracura (Myliobatiformes: Potamotrygonidae), including the description of a new species. 3 records from A new species and new record of the leafhopper genus Balclutha (Hemiptera: Cicadellidae: Deltocephalinae) from China with key to species. 38 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 2 records from Adelopsis diabolica, a new species of Ptomaphagini (Coleoptera: Leiodidae Cholevinae) from São Paulo State, Brazil. 1 records from Protozoa ZMK. 5 records from A new genus and species of Sclerodactylidae (Echinodermata: Holothuroidea: Sclerothyoninae) from the Pacific coast of Panama, and assignment of Neopentamera anexigua to Sclerothyoninae. 3 records from Five new species of the tribe Gyrophaenina Kraatz 1830 (Coleoptera: Staphylinidae: Aleocharinae) from the southern part of the United States. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 81 records from The West Palaearctic Pseudodineura and Endophytus species (Hymenoptera, Tenthredinidae). 202 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 23048 records from Herpetology Collection. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 18 records from Cladistic analysis and description of a new species of the Brazilian genus Atlantodesmus Hoffman, 2000 (Diplopoda: Polydesmida: Chelodesmidae). 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 4 records from Descriptions of three new species of Odonata from Brazil. 1240 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 2 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 2 records from Afroanomalia pseudoclistopyga, a new genus and species of pimpline parasitoid wasp (Hymenoptera: Ichneumonidae: Pimplinae) from the Afrotropical region. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 122 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 90777 records from URM - Herbário Pe. Camille Torrand. 2 records from Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México. 3 records from Species of Wadicosa (Araneae, Lycosidae): a new species close to W. quadrifera (Gravely) from the Western Ghats, India. 8840 records from ZMMU MSU, White Sea Branch. 3 records from Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 71 records from Review of the Poecilimon (Poecilimon) zonatus species group and description of new species from Turkey with data on bioacoustics and morphology (Orthoptera: Phaneropterinae). 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 55 records from A revision of the New Zealand weevil genus Irenimus Pascoe, 1876 (Coleoptera: Curculionidae: Entiminae). 246 records from Rotifers of Macquarie Island. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 6 records from The genus Thelepus Leuckart, 1849 (Annelida, Thelepodidae) in Brazil, with a redescription of the holotype of T. setosus (Quatrefages, 1866). 2 records from A new diminutive sisorid catfish (Actinopterygii: Siluriformes) from northeastern India. 1 records from Rediscovery of Terebratulina austroamericana Zezina, 1981 (Brachiopoda: Cancellothyrididae) from off northern Chile. 10 records from The type specimens of Trichomycterus alternatus (Eigenmann, 1917) and Trichomycterus zonatus (Eigenmann, 1918), with elements for future revisionary work (Teleostei: Siluriformes: Trichomycteridae). 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 11 records from Allopatric color forms of Scaphidium morimotoi Löbl, 1982 (Coleoptera, Staphylinidae, Scaphidiinae) endemic to the Amami Islands, the Ryukyus, Japan. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 1 records from Zur Kenntnis der Lithobiiden. 37 records from Revisionary systematics of the endemic soft coral fauna (Octocorallia: Alcyonacea: Alcyoniina) of the Agulhas Bioregion, South Africa. 15 records from Three species of Reteporella (Bryozoa: Cheilostomata) in a diapiric and mud volcano field of the Gulf of Cádiz, with the description of Reteporella victori n. sp. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 1 records from Revision of the Early Ordovician (late Tremadocian; Stairsian) cheirurid trilobite Tesselacauda Ross, with species from the Great Basin, western USA. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 2107 records from ZUEC-ARA - Coleção de Aracnideos do Museu de Zoologia da UNICAMP. 91255 records from PACA-AGP - Herbarium Anchieta. 35 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 66 records from Review of the genus Carlschoenherria (Coleoptera: Scarabaeidae: Melolonthinae) of the Philippines. 3 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 22166 records from Natural History Museum Maastricht (NL) - Herbarium. 5 records from A new genus and species of Aoridae (Amphipoda, Senticaudata), Propejanice lagamarensis gen. nov. sp. nov. from Brazil. 50 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae. 9404 records from MZL Invertebrate Collections. 1303 records from Crustacean specimens of Bihoro Museum. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 17 records from New genus and species of cockroaches from the tribe Brachycolini (Blattaria Blaberidae: Blaberinae) and redescription of the Hormetica strumosa. 10 records from Description of three new troglobiontic species of Cybaeodes (Araneae, Liocranidae) endemic to the Iberian Peninsula. 148 records from Other Arachnida collection of National Museum of Nature and Science. 17114 records from Collection of Coleoptera. 5408 records from Invertebrates of the river Tana Basin in Kenya available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section. 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 8853 records from Vascular Plants Collection of National Museum of Nature and Science. 12 records from A new species of Sextonia Chevreux, 1920 (Crustacea: Amphipoda: Liljeborgiidae) from the Okhotsk Sea. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 17920 records from List of the specimens of the Vanuatu National Herbarium (PVNH). 1372 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1035 records from Genus Medicago (Fabaceae) in CSBG Herbarium collections (NS, NSK). 2 records from Designation of a neotype for Clorindaia hecaloides Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Faltalini). 691 records from Barcant Butterfly Collection - Lycaenidae. 9 records from Two new species of Hippolyte from the Tropical Central and East Atlantic (Crustacea, Decapoda, Caridea). 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 29 records from Hypostomus velhochico, a new keeled Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio São Francisco basin in Brazil. 12 records from Description of a new catfish, Silurus tomodai (Siluriformes: Siluridae) from central Japan. 859118 records from Queensland Museum provider for OZCAM. 10267 records from Bruce Bennett Herbarium (BABY). 44 records from Description of the larvae and pupae of eight species of the tribe Sitonini Gistel, 1848 (Coleoptera, Curculionidae) from Central Europe. 16 records from Proposal of Kupiuka and Plesiopiuka, two new genera of jumping spiders from Brazil (Araneae: Salticidae: Heliophaninae). 2 records from Phylogenetic structure of Holbrookia lacerata (Cope 1880) (Squamata: Phrynosomatidae): one species or two?. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 1 records from Description of the pupa of Culex (Culex) bidens Dyar (Diptera: Culicidae). 3 records from Review of the rare and little-known Chinese species of the family Taeniopterygidae (Plecoptera), with description of two new species of Kyphopteryx. 895 records from Códigos de barras de hongos ectomicorrízicos de localidades selectas del neotrópico mexicano. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 11392 records from Danish Plant Bugs (Miridae). 3 records from Two new species of Tydeidae (Acari: Prostigmata) associated with stingless bees. 101 records from The genus Setodes Rambur (Trichoptera, Leptoceridae) in Japan. 18571 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 71 records from Morphology and taxonomy of the orb-weaving spider genus Mecynogea, and a peculiar species of Argiope (Araneae, Araneidae). 27 records from Two new dragonflies (Odonata: Anisoptera) from the Miocene of Carinthia (Austria). 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 16 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 6077 records from Vascular plant specimens of Iida City Museum. 3 records from Three New Spiders of the Families Clubionidae, Liocranidae and Gnaphosidae (Arachnida, Araneae) from Vietnam. 166 records from Catalogue and type designations for New Zealand Goniaceritae (Coleoptera: Staphylinidae: Pselaphinae). 194 records from Revision of the Traumatomutilla americana species group (Hymenoptera: Mutillidae). 141 records from Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 62 records from Revision of early taxa of Australian gall midges (Diptera: Cecidomyiidae). 17 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 59 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1 records from A new species of Notaepytus Skelley, 2009 (Coleoptera: Erotylidae: Tritomini) from Dominican amber. 4 records from Redescription of Micaria beaufortia (Araneae, Gnaphosidae), with notes on Afrotropical Micaria. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 3 records from Exostoma tibetana, a new glyptosternine catfish from the lower Yarlung Tsangpo River drainage in southeastern Tibet, China (Siluriformes: Sisoridae). 118 records from Taxonomic revision of the genus Xenogryllus Bolívar, 1890 (Orthoptera, Gryllidae, Eneopterinae, Xenogryllini). 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 19051 records from DMNS Mammal Collection (Arctos). 6959 records from Bird collection NTNU University Museum. 179 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 11169 records from Akita Prefectural Museum, Hiroki Watanabe Collection. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 58 records from Newhaven Sanctuary observations. 3 records from A new species of Hebrus (Hemiptera: Heteroptera: Hebridae) from Argentina. 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 82 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 26835 records from Herbario Pontificia Universidad Javeriana. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 7 records from Synopsis of the shore bugs of China (Hemiptera: Heteroptera: Leptopodomorpha: Saldidae). 11 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 181 records from Colección Ornitológica Museo de Ciencias Naturales “Lorenzo Scaglia" (MMPOr) Mar del Plata, Argentina.. 458 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 42 records from The genus Cryptotendipes Beck et Beck in Florida, with the description of a new species (Diptera: Chironomidae: Chironominae). 14 records from First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species. 3 records from A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran. 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 254 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 53 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 5 records from Dolichopodidae of riverbeds and springs in Croatia with an updated checklist of Croatia (Diptera). 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 5 records from A new species of Rhigognostis (Lepidoptera, Plutellidae) from the Canary Islands. 6065 records from LISU Herbario Angola. 16756 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 78575 records from AM: Freshwater Invertebrates (1900-2005). 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 12 records from An inordinate fondness for Osedax (Siboglinidae: Annelida): Fourteen new species of bone worms from California. 2 records from A review of the ant genus Harpegnathos Jerdon, 1851 (Hymenoptera: Formicidae) in the Philippines, with the description of two new species. 9 records from A review of Newportia species in the subgenus Newportides Chamberlin, 1921 (Scolopendromorpha, Scolopocryptopidae, Newportiinae). 5000 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 4 records from Taxonomy of two endemic Indian skinks, Eutropis bibronii (Gray, 1838) and E. nagarjunensis (Sharma, 1969) (Reptilia: Scincidae), including redescriptions of their types. 21224 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 5 records from Annelida specimens of Ryukyu University Museum (Fujukan). 10 records from A new record of Siler collingwoodi (Araneae: Salticidae) from Japan. 566 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán. 236 records from The Echinoderm Fauna of the Azores (NE Atlantic Ocean). 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 2 records from A new species of Deutella Mayer 1890 (Crustacea: Amphipoda) from the Mexican Pacific coast. 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 61 records from Photo images, 3D/CT data and mtDNA of the freshwater mussels (Bivalvia: Unionidae) in the Kyushu and Ryukyu Islands, Japan, with SEM/EDS analysis of the shell. 3 records from A new species of fan-throated lizard of the genus Sitana Cuvier, 1829 from coastal Kerala, southern India. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 14 records from Three new species and three new records of the genus Bamboosiella from China (Thysanoptera: Phlaeothripidae). 3 records from Begonia elachista Moonlight & Tebbitt sp. nov., an enigmatic new species and a new section of Begonia (Begoniaceae) from Peru. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 558 records from Recursos hidrobiológicos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia BIO. 10 records from Five new species of Acanthobothrium (Cestoda: Onchoproteocephalidea) from the long-tailed butterfly ray, Gymnura cf. poecilura (Elasmobranchii: Gymnuridae) from the Persian Gulf and Gulf of Oman. 3 records from Taxonomy of the Oriental leafhopper genus Favintiga Webb (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with description of a new species from China. 4 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 2 records from The taxonomic status of Nectomys saturatus Thomas, 1897 (Cricetidae: Sigmodontinae). 1 records from Archaeomalthus - (Coleoptera, Archostemata) a ‘ ghost adult ’ of Micromalthidae from Upper Permian deposits of Siberia?. 34064 records from UF Florida Museum of Natural History Mammals. 12 records from E. E. Green’s collection of scale insects (Hemiptera: Sternorrhyncha: Coccomorpha) in The Natural History Museum, London, U. K.. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 4061 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 973 records from Zambian Bat Collections Worldwide. 28 records from A new freshwater shrimp species of the genus Palaemon Weber, 1795 (Decapoda: Caridea: Palaemonidae) from northeastern Japan. 8 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 466 records from PSU-Seagrass Collection. 8 records from One new species and two redescriptions of Marphysa (Eunicidae, Annelida) species of the Aenea-group from Australia. 1196 records from Entomological collection of the National Museum. 3 records from A new species of the armored spider genus Caraimatta Lehtinen, 1981 from Colombia (Araneae: Synspermiata: Tetrablemmidae). 51 records from Poliquetos litorales de la región norte y centro del estado de Veracruz. 6 records from New species of the genus Polyplectropus Ulmer 1905 (Insecta: Trichoptera: Polycentropodidae) from Indian Himalaya. 1 records from Miriapodi di alcune grotte della Campania. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 81889 records from Coleoptera collection, NHM. 4 records from Neocrassocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 4 records from Campydoroides manautei gen. et sp. nov. from New Caledonia and a reappraisal of the suborder Campydorina (Nematoda). 5 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 562 records from UWIZM International Lepidoptera Collection. 5 records from A new species of Conognatha Eschscholtz, 1829 (Coleoptera: Buprestidae), with new state records of the genus for Brazil. 151 records from Helmintos parásitos de peces del sureste de México. 1100 records from Proyecto de cultivo extensivo y comercialización de las mariposas de la región de Chajul, Chiapas. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 11 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 49 records from New species and new records of gelechiid moths (Lepidoptera, Gelechiidae) from southern Siberia. 255 records from Mosses and Lichens (Vermorel coll.). 26 records from Carpoteca de Frutilla del Banco de Germoplasma de Frutilla - Universidad Nacional de Tucumán, Argentina. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 4 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 3 records from New species of Poecilocloeus Bruner, 1910 (Orthoptera: Acrididae: Proctolabinae) from Paraná State, Brazil. 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 4534 records from Naturhistorisches Museum Mainz, Schmetterlingssammlung Rodenkirchen. 177 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 3 records from Three new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Taiwan. 197 records from Berlin-Brandenburg Plant Collection 2004. 10 records from Redescription of the Central American genus Moribaetis Waltz & McCafferty 1985 (Ephemeroptera, Baetidae). 3 records from The mythic species Issus analis Brullé, 1833 (Hemiptera, Fulgoroidea, Issidae): still an enigmatic taxon. 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 365 records from Colección Herpetológica de la Patagonia. 1 records from Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae). 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 38 records from On the systematic position of the genera Paraplastis Hampson, Migoplastis Felder and Dondera Moore (Lepidoptera, Erebidae, Arctiinae). 1 records from Leptanillahypodracos sp. n., a new species of the cryptic ant genus Leptanilla (Hymenoptera, Formicidae) from Singapore, with new distribution data and an updated key to Oriental Leptanilla species. 18354 records from Hokkaido University Coleoptera Collection. 1 records from Earthworm species in various land use systems in the Campos Gerais region of Lapa, Paraná, Brazil. 38 records from Comparative morphology and taxonomy of the tiger moth genus Epanycles Butler (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina), with notes on related genera. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 38 records from New species of Bacuma Cameron (Hymenoptera: Braconidae: Braconinae) from Kenya and West Darfur with a key to species. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 1 records from A new genus and species of Elcanidae (Insecta: Orthoptera) from Cretaceous Burmese amber. 2 records from A new species of Enchytraeus (Enchytraeidae, Oligochaeta) from the profundal of Lake Van, the world's largest soda Lake (Turkey, East Anatolia). 20833 records from UMNH Birds Collection (Arctos). 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 15 records from A mountain of millipedes IV: Species of Prionopetalum Attems, 1909, from the Udzungwa Mountains, Tanzania. With notes on “ P. ” fasciatum (Attems, 1896) and a revised species key (Diplopoda, Spirostreptida, Odontopygidae). 10 records from Feather mites of the genus Trouessartia Canestrini (Acariformes: Trouessartiidae) from swallows (Passeriformes: Hirundinidae) in Canada. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 3 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 6 records from Acricotopus indet. morphotype incurvatus: Description and genetics of a new Orthocladiinae (Diptera: Chironomidae) larval morphotype from the Tibetan Plateau. 250 records from Colección de Mamíferos – Universidad de la Amazonia. 35229 records from The DNA and Sample Repository at AIT. 44251 records from R - Herbário do Museu Nacional. 2905 records from Colección del Banco de Germoplasma de la Universitat de València. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 1 records from Identification of Nipaecoccus (Hemiptera: Coccomorpha: Pseudococcidae) species in the United States, with descriptions of Nipaecoccus bromelicola sp. n. and the male of N. floridensis Beardsley. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 12972 records from Insect specimens of Komatsu City Museum. 33991 records from HEPH - Herbário Ezechias Paulo Heringer. 3 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 23 records from A neotype for Pontoscolex corethrurus (Müller, 1857) (Clitellata). 11 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 6174 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 2 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 27108 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 22811 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 6 records from Stenelmis koreana Satô, 1978 (Coleoptera: Elmidae): confirmed as a wide-spread species by DNA-sequencing. 4 records from First record of Isegama Krombein (Hymenoptera, Chrysididae, Amiseginae) from China, with description of a new species. 30008 records from Lepidoptera specimen database of Japan. 1 records from A new species in the Simulium vernum group from the Alps of southern Germany: Simulium arminii (Diptera: Simuliidae). 10 records from On the spider genus Arboricaria with the description of a new species (Araneae, Gnaphosidae). 2 records from Two new species of the marine water mite family Pontarachnidae (Acari: Hydrachnidia) from the Gulf of Antalya, Turkey. 8 records from Mesene Doubleday (Lepidoptera: Riodinidae) from Parque Nacional da Serra do Divisor, Acre, Brazil, with taxonomic notes and the description of a new species. 28928 records from Collection Vermes - ZMB. 22 records from Ptyctimous mites (Acari, Oribatida) of Victoria (Australia). 7 records from Parasitoides de Cochinilla. 45 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 2 records from A new species of Prosopistoma Latreille, 1833 (Ephemeroptera: Prosopistomatidae) from South India. 20576 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ornithology National Collection (MACNOr). 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 2311 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 18 records from Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 2 - Description of two new species of Centrophorus and clarification of the status of Centrophorus lusitanicus Barbosa du Bocage & de Brito Capello, 1864. 31 records from Notes on the genus Conocephalus Thunberg, 1815 (Orthoptera: Tettigoniidae: Conocephalinae) in Southwest China with description of one new species. 622 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 203916 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 30 records from Revision of Hestiasulini Giglio-Tos, 1915 stat. rev. (Insecta: Mantodea: Hymenopodidae) of Borneo, with description of new taxa and comments on the taxonomy of the tribe. 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 3513 records from Alien Flora of Nepal at KATH. 128095 records from University of Michigan Museum of Zoology, Division of Mammals. 21884 records from Birds Specimens. 46318 records from Banco de datos florísticos del Herbario CHAP. 3 records from A new genus Gnathospinosa (Lepidoptera: Tineidae: Euplocaminae) from China, with description of a new species and its taxonomic position. 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 150 records from Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters. 67 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 107 records from Notoaturine water mites from New Zealand (Acari: Hydrachnidia: Notoaturinae) with the description of five new species. 44 records from Chaetonerius Hendel (Neriidae: Diptera) from the East African islands with description of four new species from Madagascar and the Comoros. 371 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2347 records from The communities of terrestrial macrofungi in different forest types of boreal zone in West Siberia. 18 records from Taxonomic notes, lectotype designations and new synonymies in some species of the bee genus Centris Fabricius, 1804 described by Sándor Mocsáry and Heinrich Friese (Hymenoptera: Apidae). 66 records from Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species. 4 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 31 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 3 records from Resolution of the types, diagnostic features, and distribution of two easily confused Sand Lizards, Pedioplanis laticeps (Smith, 1845) and P. burchelli (Duméril & Bibron, 1839) (Squamata: Lacertidae). 39 records from Anfibios y reptiles de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 732 records from Colección Mastozoológica de la Universidad Industrial de Santander. 2789 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 5 records from Two new species of the genus Habrobathynella Schminke, 1973 (Syncarida, Parabathynellidae) from the southwestern peninsular India. 7 records from Four new species of the subgenus Homoneura from Jiangxi Province, China (Diptera: Lauxaniidae: Homoneura). 30 records from Banco de Germoplasma de la Universidad de Salamanca. 2 records from First record of Pyramica baudueri (EMERY, 1875) (Hymenoptera: Formicidae) from Bulgaria.. 5 records from Society Islands beach bum black flies (Diptera: Simuliidae). 2346 records from Research database of Madagascar grasses compiled by Maria Vorontsova. 1 records from A new species of Andinobates (Anura: Dendrobatidae) from the Urabá region of Colombia. 2726 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 352 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 34 records from Description of the first Palaearctic species of Tineobius Ashmead, 1896 with DNA data, a checklist of world species, and nomenclatural changes in Eupelmidae (Hymenoptera, Chalcidoidea). 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 41 records from Annotated catalogue of the click-beetle tribe Senodoniini (Coleoptera: Elateridae: Dendrometrinae). 6 records from Three new Macropsini (Hemiptera: Cicadellidae) leafhopper species from Australia. 15 records from Character state variation within Dendrothrips (Thysanoptera: Thripidae) with a revision of the species from China. 1 records from Zetes latipes. 2 records from A new genus and a new species of Schizomyiina (Diptera: Cecidomyiidae: Asphondyliini) inducing petiole galls on Macaranga bancana (Miq.) in Borneo, Malaysia. 112471 records from Finnish Floristic Database (University of Turku Collections). 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 2 records from Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae). 64 records from Copelatus Erichson, 1832 from Maharashtra, India, with description of three new species and notes on other taxa of the genus (Coleoptera: Dytiscidae: Copelatinae). 35 records from Reptiles Specimens of Akita Prefectural Museum. 17625 records from Ibaraki Nature Museum, Lichen collection. 7113 records from Primera fase de actualización de la Colección de Siphonaptera Alfredo Barrera del Museo de Zoología Alfonso Herrera. 339 records from UWIZM Snakes. 5 records from Notes on the Neotropical leafhopper subgenus Amplicephalus (Nanctasus) Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with description of two new species. 20327 records from Herbier du Muséum d'Angers. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 395 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 2 records from A new species of Lucasioides Kwon (Isopoda: Oniscidea: Agnaridae) from China. 1 records from Oppia glaucina. 10 records from Catalogue of Ampulicidae, Crabronidae and Sphecidae of Iran (Hymenoptera, Apoidea). 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 1 records from Seven new species of Night Frogs (Anura, Nyctibatrachidae) from the Western Ghats Biodiversity Hotspot of India, with remarkably high diversity of diminutive forms. 151 records from Morphological revision of the Subgroup 1 Fauchald, 1970 of Marphysa de Quatrefages, 1865 (Eunicidae: Polychaeta). 4 records from Crustáceos del municipio Santa Bárbara, Santander - Proyecto Santander BIO. 1 records from Brachiopods Specimens of Akita Prefectural Museum. 37 records from Notes on the Dianous aereus complex with description of a new species (Coleoptera, Staphylinidae). 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 188 records from Australian Diplectroninae reviewed (Insecta: Trichoptera), with description of 21 new species, most referred to a new genus. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 54451 records from FUEL - Herbário da Universidade Estadual de Londrina. 30 records from A review of the Lecithoceridae (Lepidoptera: Gelechioidea) of southern Africa, based on type specimens deposited in the Ditsong National Museum of Natural History (TMSA), with descriptions of three new species. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 240635 records from Dataflos. 83981 records from UTEP Plants (Arctos). 26 records from Halocosa gen. n., a new genus of Lycosidae (Araneae) from the Palaearctic, with a redescription of H. cereipes (L. Koch, 1878). 175 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 15 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from A bizarre Jurassic maniraptoran theropod with preserved evidence of membranous wings. 8 records from Mecklenburg-Brandenburg Plant Collection 2008. 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 2 records from Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in an intertidal seagrass bed on the coast of the Andaman Sea, Thailand, with reference to the taxonomic status of the genus Trichotheristus Wieser, 1956. 87 records from Five new records and an annotated checklist of the leeches (Annelida: Hirudinida) of Iran. 1151 records from Intermountain Herbarium Lichen Collection (Utah State University). 72399 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 7880 records from Algaterra Types. 1 records from Cepolacanthus kimi, a new genus and species of copepod (Cyclopoida: Taeniacanthidae) parasitic on Bandfish Acanthocepola abbreviata (Valenciennes, 1835) (Actinopterygii: Cepolidae) caught off the Iraqi coast. 327284 records from Fungi (S). 7 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 1 records from Hoplophora longula. 143 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 1 records from Simulium (Gomphostilbia) lemborense, a new black fly species (Diptera: Simuliidae) from Flores, Indonesia. 30797 records from NCSM Mollusks Collection. 5 records from Description of two new species of Dima Charpentier, 1825 from China (Coleoptera: Elateridae: Dendrometrinae). 2 records from A new synonym of Neomida luteonotata (Pic, 1926) (Coleoptera: Tenebrionidae: Diaperini). 802 records from Situación actual de ocho especies de anfibios en categoría de riesgo en Veracruz. 16 records from Lepidurus arcticus survey Northeast Greenland 2013. 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 2608 records from Butterflies of the Rupununi. 35 records from New records of Chalcidoidea (Hymenoptera) from the Maltese Islands with an updated checklist. 23 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 1 records from Nothrus palliatus. 7462 records from Ibaraki Nature Museum, Fungi collection. 68 records from A systematic revision of the genus Gnophopsodos Wehrli, 1945, with description of two new species (Lepidoptera: Geometridae). 10160 records from UAM Fish Collection (Arctos). 158 records from Museu Paraense Emilio Goeldi - Acari Collection. 1165 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 8808 records from Survey of bumblebees in central Alberta - 2018. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 11 records from Review of the sulcacitus group of Euschistus (Pentatomidae: Pentatominae: Carpocorini) with description of the internal female genitalia and a new species. 11772 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 86 records from Checklist of the earthworms (Oligochaeta) of Kerala, a constituent of Western Ghats biodiversity hotspot, India. 3171 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 3 records from A new species of Victoriopisa bantenensis (Crustacea: Amphipoda: Eriopisidae) from West Java, Indonesia. 33 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 3 records from A new species of Amphinemura (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 6 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 325 records from Review of Dissomphalus Ashmead (Hymenoptera, Bethylidae) from Panama, with key to the Central American species. 4 records from Two new and one newly recorded species of Corinnidae and Liocranidae from Taiwan (Arachnida: Araneae). 18454 records from UCM Mammal Collection (Arctos). 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 3187 records from Sedges of the Forest Herbarium Ibadan (FHI) Nigeria. 271952 records from Natural History Museum, Vienna - Herbarium W. 7 records from On the huntsman spider genus Vi
Keywords: GBIF; biodiversity; species occurrences